ESG Disclosure on Stock Prices: The Moderating Role of Profitability in Manufacturing Companies - Hidayasya Nur Afifah; Theresia Tyas Listyani (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2026)
AbstractThis study is motivated by the underperformance of ESG indices relative to the Composite Stock Price Index (IHSG) in 2024, indicating that sustainability practices are not optimally valued in Indonesia’s short-term, retail-dominated capital market. Consequently, this research aims to analyze the effect of specific Environmental, Social, and Governance (ESG) disclosure dimensions on stock prices and examine the role of profitability as a moderator within the context of Indonesian-listed manufacturing entities. Adopting a quantitative causal associative approach, the study utilizes archival data extracted from 16 manufacturers’ annual and sustainability disclosure spanning 2022 through 2024. Through purposive sampling, 48 firm-year observations were obtained and examined through panel regression techniques via EViews 10. Result reveal that stock prices respond significantly only to governance disclosure practices, whereas environmental and social disclosure alongside profitability moderation, exhibit negligible market impact. These findings contribute to Stakeholder Theory by resolving prior inconsistencies through dimensional analysis, highlighting that the Indonesian market prioritizes immediate governance accountability over long-term sustainability. This study fills a critical gap regarding the limits of profitability moderation, offering essential implications for regulators and investors in emerging economies. Keywords: ESG Disclosure, Stock Price, Profitability, Stakeholder Theory, Manufacturing Sector